Effect of Al incorporation in nonpolar m‐plane GaN/AlGaN multi‐quantum‐wells using plasma‐assisted molecular‐beam epitaxy. Issue 9 (21st December 2016) - Lim, Caroline B.; Ajay, Akhil; Bougerol, Catherine; Bellet‐Amalric, Edith; Schörmann, Jörg; Beeler, Mark; Monroy, Eva
Abstract : This paper assesses the difficulties associated with Al incorporation in nonpolar m ‐plane GaN/AlGaN multi‐quantum‐wells grown on free‐standing m ‐plane GaN. Structures with average Al mole fraction below 6% show atomically flat surfaces and no extended structural defects, in spite of alloy fluctuations up to 30% of the average concentration. Increasing the average Al composition of the alloy above 23% induces anisotropic degradation of the surface morphology, with appearance of elongated features which increase the surface roughness, along with formation of stacking faults, dislocations, and nm‐sized Al‐rich clusters. The effect of all these structural features on the MQWs optical performance is discussed.